Introductory econometrics: using monte carlo simulation with microsoft excel / by Humberto Barreto and Frank M. Howland - Barreto, Humberto; Howland, frank M. (ed.) (New Delhi, 2009)
This highly accessible and innovative text and accompanying CD-ROM use Excel (R) workbooks powered by Visual Basic macros to teach the core concepts of econometrics without advanced mathematics. It enables students to run Monte Carlo simulations in order to understand the data generating process and sampling distribution. Intelligent repetition of concrete examples effectively conveys the properties of the ordinary least squares (OLS) estimator and the nature of heteroskedasticity and autocorrelation. Coverage includes omitted variables, binary response models, basic time series, and simultaneous equations. The authors teach students how to construct their own real-world data sets drawn from the internet, which they can analyze with Excel (R) or with other econometric software. The Excel add-ins allow students to draw histograms, to compute P-values and robust standard errors, and to construct their own MonteCarlo and bootstrap simulations. For more readers may visit the web site at www.wabash.edu/econometrics.
Keywords: Econnometrics